Annexin 1: differential expression in tumor and mast cells in human larynx cancer. - Silistino-Souza, R; Rodrigues-Lisoni, F; Cury, P; Maniglia, J; Raposo, L; Tajara, E; Christian, H; Oliani, S (2007)
Annexin 1 protein (ANXA1) expression was evaluated in tumor and mast cells in human larynx cancer and control epithelium. The effect of the exogenous ANXA1 (peptide Ac 2-26) was also examined during the cellular growth of the Hep-2 human larynx epidermoid carcinoma cell line. This peptide inhibited the proliferation of the Hep-2 cells within 144 hr. In surgical tissue specimens from 20 patients with larynx cancer, ultrastructural immunocytochemistry analysis showed in vivo down-regulation of ANXA1 expression in the tumor and increased in mast cells and Hep-2 cells treated with peptide Ac2-26. Combined in vivo and in vitro analysis demonstrated that ANXA1 plays a regulatory role in laryngeal cancer cell growth. We believe that a better understanding of the regulatory mechanisms of ANXA1 in tumor and mast cells may lead to future biological targets for the therapeutic intervention of human larynx cancer.